Comparison of the Effectiveness of Relational Imagery Therapy and Acceptance and Commitment Therapy on We-Ness Experience in Women Exposed to Marital Infidelity - Ghasemnejhad, Kiana; Sadati, Seyedeh Zahra (KMAN Counseling & Psychology Nexus, 2027)
The aim of the present study was to examine the effectiveness of relational imagery therapy and acceptance and commitment therapy on we-ness experience in women exposed to marital infidelity. This study was conducted using a quasi-experimental method with a three-stage pretest, posttest, and three-month follow-up design, including a control group. The statistical population included all women aged 25 to 45 years who referred to Sina Counseling Center in Nowshahr and had experienced marital infidelity. Among them, 45 participants were selected purposively based on the inclusion criteria and were then randomly assigned to three groups of 15 participants each: relational imagery therapy, acceptance and commitment therapy, and control group. The data collection instrument was the We-Ness in Couple Relationships Questionnaire (Cruz et al., 2023). Each experimental group received its respective intervention in eight 90-minute sessions, held twice a week. The posttest was administered immediately after the intervention, and the follow-up phase was conducted three months later. The data were analyzed using multivariate mixed analysis of variance. The results showed that relational imagery therapy was more effective than acceptance and commitment therapy in enhancing we-ness experience (p < .05). These findings, while explaining the importance of relational imagery-based therapeutic interventions in improving the emotional and functional indicators of women harmed by marital infidelity, emphasize the necessity of applying this approach in couple counseling services.